Profile of Mathematics Reasoning of Junior High School Students in Solving Mathematical Problems Based on Auditory Learning Style - La Sahija; Rizal Rizal; Wa Ode Nining Setiyawan; Aufal Kausar (Universitas Muhammadiyah Malang, 2026)
Mathematical reasoning is an important competency in junior high school mathematics learning, but learning and evaluation are still more focused on the final result than the student's thinking process. In addition, studies on the relationship between auditory learning styles and students' mathematical reasoning profiles are still limited, especially in revealing students' thinking processes in depth. This study aims to describe the mathematical reasoning profile of junior high school students based on auditory learning styles in solving mathematical problems. This study uses a descriptive qualitative approach with the subjects of six grade VII students of SMP Negeri 18 Buton, which consist of high, medium, and low hearing categories. Data were collected through learning style questionnaires, written tests, and semi-structured interviews, then analyzed using the Miles and Huberman models. The results showed that students in the high auditory category had more consistent reasoning skills in the aspects of making assumptions, mathematical manipulation, drawing conclusions, and checking the validity of arguments. Middle category students need verbal reinforcement at several stages, while lower category students experience difficulties in evaluative and argumentative aspects. This study emphasizes the importance of learning strategies based on verbal discussions, scaffolding, and multimodal assessments to optimally develop students' mathematical reasoning skills.